Penerimaan Khalayak Terhadap Pertukaran Peran Gender antara Laki-laki dan Perempuan dalam Sinetron Dunia Terbalik di RCTI - Ratnasari, Hesti; Noor Rakhmad, Wiwid (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2018)
This research is conducted based on the new idea of cultural contstruction regarding gender’s role between man and woman constructed into a soap opera entitled Dunia Terbalik where the role of both genders are switched, and thus very different from the dominant idea believed by Indonesian society which is patriarchy. The objective of the research is to describe the difference between media text meaning found in Dunia Terbalik soap opera and the meaning conceived by the audience. The researcher has to determine the dominan meaning by using textual analysis. The society acceptance while doing media text reading based on reception analysis argued by Stuart Hall. The finding of the research shows that all informant did the negotiated position regarding the exchanged role which is contructed in Dunia Terbalik soap opera. In the specific part they agreed about the switched role found in the soap opera, but in the some parts they disagreed. So, the gender’s role between man and woman which has been constructed all this time has been reshuffled because of the people’s acceptance about the switched gender’s role acceptance has slightly changed positively. Eventhough in this research female informant tend to respond toward the gender’s role switch more rigidly than the male informant. The female informant is still holding on the idea of man as breadwinner. The male informant is more openly accepting the idea of gender’s role switch and woman as breadwinner than woman did. Some informants also argued that there should be an equality of both genders so one does not become a burden to the other. Furthermore, the society background has become one sigificant factor that influencing the way the audience conceive and contruct the media text discourse.